Preparing correctional settings for the next pandemic: a modeling study of COVID-19 outbreaks in two high-income countries - Kwon, Jisoo A.; Bretaña, Neil A.; Kronfli, Nadine; Dussault, Camille; Grant, Luke; Galouzis, Jennifer; Hoey, Wendy; Blogg, James; Lloyd, Andrew R.; Gray, Richard T. (Frontiers in Public Health, 2024)
Introduction Correctional facilities are high-priority settings for coordinated public health responses to the COVID-19 pandemic. These facilities are at high risk of disease transmission due to close contacts between people in prison and with the wider community. People in prison are also vulnerable to severe disease given their high burden of co-morbidities. Methods We developed a mathematical model to evaluate the effect of various public health interventions, including vaccination, on the mitigation of COVID-19 outbreaks, applying it to prisons in Australia and Canada. Results We found that, in the absence of any intervention, an outbreak would occur and infect almost 100% of people in prison within 20 days of the index case. However, the rapid rollout of vaccines with other non-pharmaceutical interventions would almost eliminate the risk of an outbreak. Discussion Our study highlights that high vaccination coverage is required for variants with high transmission probability to completely mitigate the outbreak risk in prisons.